Piper betle L. Leaves Extract Potentially Reduce the Nitric Oxide Production on LPS-Induced RAW 264.7 Cell Lines - Dwijayanti, Dinia Rizqi; Puspitarini, Sapti; Widodo, Nashi (Graduate School, Universitas Brawijaya, 2023)
Chronic inflammation can lead to several diseases that represent the leading causes of mortality worldwide. Conventional treatment of inflammation can carry some risks. Therefore, research on herbal medicine that are suspected of having anti-inflammatory effects, such as Piper betle L., is important. This study aims to investigate the effect of P. betle L. extract on nitric oxide as a pro-inflammatory mediator. The dried leaves of P. betle L. were extracted by ethanol. RAW 264.7 cells were treated with LPS and P. betle L. extract (PBE). Nitric oxide was measured by the Griess method. Antioxidant activity was determined using 2,2–Diphenyl-1-picrylhydrazyl (DPPH) method. Total flavonoids and phenolic content were also identified by aluminium chloride and Folin–Ciocalteu colorimetric assay, respectively. This study demonstrated that the PBE has excellent NO suppression activity with the IC50 56.22±16.41 μg.mL-1, without cytotoxicity. PBE also has DPPH inhibitory concentration IC50 values of 279.67±11.36 ppm. Interestingly, PBE has a flavonoid content of 50.17±3.14 mg QE.g-1 and phenolic content of 128.92±1.2 mg GAE.g-1. These compounds are thought to be responsible for its anti-inflammatory as well as antioxidant. This study proved that P. betle L. leaves extract could be used as a candidate for anti-inflammatory drugs. Nevertheless, further research about the biological activity mechanism and their bioactive compounds' purification is still required. Keywords: Inflammation, lipopolysaccharide, Macrophage, Nitric Oxide, Piper betle.